Licochalcone E reduces chronic allergic contact dermatitis and inhibits IL-12p40 production through down-regulation of NF-kappa B - Cho, Young-Chang; Lee, Sung Ho; Yoon, Goo; Kim, Hyung-Seok; Na, Joo Young; Choi, Hyun Jin; Cho, Cheng-Weon; Cheon, Seung Hoon; Kang, Bok Yun (ELSEVIER SCIENCE BV, 2010)
Licochalcone, a constituent of licorice, has antitumor, antimicrobial, and anti-inflammatory effects. Recently, licochalcone E was isolated from the roots of Glycyrrhiza inflata and its biological functions are not fully examined. In this study, we investigated its ability to modulate production of IL-12p40, a common subunit of IL-12 and IL-23. Licochalcone E dose-dependently inhibited IL-12p40 production from lipopolysaccharide-stimulated RAW264.7 macrophage cells. The repressive effect was mapped to a region in the IL-12 gene promoter containing a binding site for NF-kappa B. Furthermore, licochalcone E decreased binding to the NF-kappa B site in RAW264.7 macrophage cells. Using a chronic allergic contact dermatitis model induced by repeated application of oxazolone, we showed that licochalcone E inhibited the increased IL-12p40 expression and ear thickness induced by oxazolone. Taken together, licochalcone E inhibits IL-12p40 production and has therapeutic potential to reduce skin inflammation. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: GLYCYRRHIZA-INFLATA; T-CELLS; PARASITE MITOCHONDRIA; PSORIASIS-VULGARIS; INTERFERON-GAMMA; INTERLEUKIN-12; CYTOKINE; IL-23; P40; EXPRESSION